Consortium for direct seeded rice for Asia - CGIAR Research Program on Rice (2019)
Established in December 2017, the DSRC launched on 6th February 2018 at IRRI. A Field Laboratory was established at IRRI, Philippines, IRRI South Asia Regional Center (ISARC), India, and at CARDI, Cambodia. In India, 12 research centers participate. The first annual review and planning meeting was on March 13-14, 2019.